Learning Media Using Camtasia Studio 8 Video to Improve Student Learning Outcomes in Basic Schools - Iin Indrayani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research is a Classroom Action Research (CAR) which consists of two cycles. The research subjects were fourth grade students in class IV C Al Azhar 22 Islamic Elementery School Salatiga, Central Java with the total of students are 24 students. The Data collection techniques using test and non-test techniques. The assessment instrument used items and observations of the scoring rubric. Analysis of the data used in the study included a comparative descriptive technique, namely a statistical technique by comparing the scores between cycles, the mean, the minimum score, the maximum, and the percentage.The results of the study that used the video powerpoint Camtasia Studio 8 media can improve student learning outcomes in the Theme 5 My Hero class IV C Al Azhar 22 Islamic Elementery School Salatiga. The conclusion of this study that used the video powerpoint of Camtasia Studio 8 media can improve student learning outcomes in the theme 5 My Hero class IV C Al Azhar 22 Islamic Elementery School Salatiga. And the suggestions for the teachers, they should be able to use the Camtasia Studio 8 powerpoint media according to the steps in thematic subjects, so that it can improve the active participation from students, generate ideas, mastery of concepts and can improve students thematic learning outcomes.